Amplitude of Low-Frequency Oscillations in Major Depressive Disorder With Childhood Trauma - Wu, Zhuoying; Luo, Qianyi; Wu, Huawang; Wu, Zhiyao; Zheng, Yingjun; Yang, Yuling; He, Jianfei; Ding, Yi; Yu, Rongjun; Peng, Hongjun (Frontiers in Psychiatry, 2021)
Major Depressive Disorder (MDD) with childhood trauma is a functional subtype of depression. Frequency-dependent changes in the amplitude of low-frequency fluctuations (ALFF) have been reported in MDD patients. However, there are few researches on ALFF about major depressive disorder with childhood trauma. Resting-state functional magnetic resonance imaging was used to measure the ALFF in 69 Major Depressive Disorder (MDD) patients with childhood trauma (28.7 ± 9.6 years) and 30 age-matched healthy controls (28.12 ± 4.41 years). Two different frequency bands (slow-5: 0.010–0.027 Hz; slow-4: 0.027–0.073 Hz) were analyzed. Compared with controls, the MDD with childhood trauma had decreased ALFF values in left S1(Primary somatosensory cortex), and increased ALFF values in left insula. More importantly, significant interactions were found between these frequency bands and the two groups in right dorsal anterior cingulate cortex (dACC). Our finding may provide insights into the pathophysiology of MDD with childhood trauma.